Marwān ibn Janāḥ: on the nomenclature of medicinal drugs (Kitāb al-talkhīṣ) : edition, translation and commentary, with special reference to the Ibero-Romance terminology - Ibn Janāḥ, Abū al-Walīd Marwān, approximately 990-approximately 1050, (Islamic History and Civilization ;, 2020)
In early eleventh century Zaragoza, the eminent Jewish scholar Abū l-Walīd Marwān ibn Janāḥ wrote a glossary containing almost 1100 entries, entitled Kitāb al-Talkhīṣ . This important text, considered lost until recently, contains Arabic and foreign-language names of simple drugs, weights, measures, and other medical terms. In the present volume, the Kitāb al-Talkhīṣ is edited and translated for the first time by Gerrit Bos and Fabian Käs. In detailed commentaries, the editors identify the substances mentioned in the Talkhīṣ . They also elaborate on the role of the text in the history of Arabic glossaries concerned with medical nomenclature. Special attention is paid to Ibn Janāḥ's Ibero-Romance phytonyms, analysed in depth by Mailyn Lübke and Guido Mensching.